Impact of cognitive-behavioral therapy on daily living skills of high functioning autistic children with anxiety disorders - Atallah Alenezi; Khadiga Abd-Elgied Gomea Gomea Hassan; Tahany El-Sayed El-Sayed Amr; Abdulellah Alsolais (Smujo International, 2021)
Abstract. Alenezi AK, Hassan KAG, Amr TEE, Alsolais A. 2021. Impact of cognitive-behavioral therapy on daily living skills of high functioning autistic children with anxiety disorders. Nusantara Bioscience 13: 41-46. Cognitively Behavioral Therapy (CBT) is a psychotherapeutic intervention that is used to improve mental health. It is known to have positive effect on the daily living skills of autistic children with anxiety disorders. The aim of the current study was to evaluate the effect of cognitive-behavioral therapy on daily living skills of high functioning autistic children with anxiety disorders. A Quasi-experimental research design was adopted in this research. A purposive sample of 100 autistic children (50 in intervention group and 50 in control group) aged between 7-8 years were included in this study. Three main tools were used: Vineland Adaptive Behavior Scale used to measure the everyday living skills of children, Parent-Child Interaction Questionnaire (PACHIQ), and Diagnostic and Statistical Manual of Mental Disorders (DSM-V) for assessing anxiety disorder in children and adolescents 6-18 years. The results showed an improvement in children’s daily life skills and slight reductions in caregiver’s participation in the daily life skills of children. There was a significant difference between intervention group and control groups (p < 0.001). The current results exhibit that CBT may help in increasing autistic children's independence towards daily living skills.